Implementing Guided Inquiry-Based Biology Learning Tools to Enhance Students' Critical Thinking Skills - Ali Ali; Rafiqa Rafiqa; Effendi Dg Palliwi; Nuraini Nuraini; Rahmadiani Rahmadiani (Jurnal Penelitian Pendidikan IPA, 2023)
The implementation of biology learning in high school focuses more on mastering concepts and minimal processes. This can be seen from the tendency of teachers to use more teacher-oriented learning. This condition also occurs in SMA Negeri 4 Palu, causing low students' critical thinking skills. This study aims to implement guided inquiry-based biology learning tools to improve students' critical thinking skills on the respiratory system material. This research is a quantitative descriptive research with one group pretest-posttest design. This research involved 30 students of class XI SMA Negeri 4 Palu. The learning tools implemented in this study are lesson plans, student worksheets, and learning materials. Test instruments in the form of multiple choices and descriptions are used to measure cognitive learning outcomes and students' critical thinking skills. The implementation of learning and student learning activities were also identified in this study using observation sheets carried out by 2 observers. Data were analyzed descriptively using the n-gain equation. Based on the results of the study it was found that (a) the implementation of learning was good (3.6); (b) The frequency of activities that stand out is that they can improve students' critical thinking skills (c) positive student responses (82); (d) students' critical thinking skills increased (N-gain; 0.76 with high criteria). Based on the results of the study it can be concluded that the guided inquiry learning model can improve the critical thinking skills of class XI students at SMA Negeri 4 Palu